Teks Vista: Kemampuan Menyimak Siswa Melalui Media Pembelajaran TV Putar - Silvia Permatasari; Zahra Zahra; Nurul Fadhilah; Dewi Sintiya; Mawaddah Warahmah; Milati Ramadhan M; Juandono Juandono; Raehan Kamil; Adrimus Adrimus; Arif Ardiansyah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This research evaluates the effectiveness of playback TV media in improving students' listening skills at SD 012 Kampung Panjang. Qualitative methods with classroom observations were used to collect data related to student interactions with this media. The research results show that rotating TV can increase students' motivation and involvement in listening learning. This media offers an interesting and realistic learning experience, even though there are obstacles. This research suggests the use of rotating TV and active interaction after listening as effective strategies in language learning.